Burtu apguve 5-6 gadu vecumā pirmsskolas izglītības iestādē - Reinsone, Linda (Latvijas Universitāte, 2010)
Lindas Reinsones pētījumā tiek apskatīta un analizēta burtu apguve 586 gadu vecumā pirmsskolas izglītības iestādē. Pētījuma teorētiskajā daĜā balstoties uz psihologa Ž. Piažē teoriju, pedagoăijas zinātnieku – D. Lieăenieces, Ā. Ptičkinas, S. Tūbeles un psihologu – D. ElkoĦina, G. Svences un I. Puškareva atziĦām, autore analizē burtu apguvi un lasītprasmi, lasītmācīšanās metodes un paĦēmienus, pirmsskolas vecuma bērnu, 586 gadi, attīstību. Pētījuma empīriskajā daĜā autore analizē, kā burtu mācīšanas metodiskie paĦēmieni ietekmē burtu apguves procesu 5 – 6 gadu vecumā pirmsskolas izglītības iestādē X. Izstrādāto teorētisko un empīrisko pētījumu, iespējams izmantot pirmsskolas izglītības iestādē darbā ar bērniem, apgūstot burtus un lasītprasmi. Atslēgvārdi: burtu apguve, lasītprasme, bērns 5 – 6 gadu vecumā, veseluma pieeja.

In Linda Reinsone’s research letters’ acquirement by 586 years old children in preschool educational institution is overviewed and analyzed. In the theoretical part of the study the author analyses letters’ acquirement and reading literacy, methods and techniques of reading teaching, preschool age (586 years old) children’s development. Her study is based on psychologist Piazhe theory as well as on pedagogics scientists’ 8 D. Liegeniece’s, A. Ptichkina’s, S. Tubele’s and psychologists’ 8 D. Elkonina, G. Svence’s un I. Pushkareva conclusions. In the empirical part of the research the author analyses how letter teaching methodological techniques influence letters’ acquirement process in 5 86 years old children in the preschool educational institution X. The elaborated theoretical and empirical study can be used in preschool educational institutions working with children acquiring letters and reading literacy. Keywords: letters’ acquirement, reading literacy, 5 – 6 years old children, entirety approach.
Acquisition of letters at the age of 5-6 at preschool
Keywords: Pedagoģija